1997
DOI: 10.1302/0301-620x.79b4.0790583
|View full text |Cite
|
Sign up to set email alerts
|

Early Radiological Observations May Predict the Long-Term Survival of Femoral Hip Prostheses

Abstract: We reviewed a consecutive series of 527 uninfected hip replacements in patients resident in the UK which had been implanted from 1981 to 1993. All had the same basic design of femoral prosthesis, but four fixation techniques had been used: two press-fit, one HA-coated and one cemented. Review and radiography were planned prospectively. For assessment the components were retrospectively placed into two groups: those which had failed from two years onwards by aseptic femoral loosening and those in which the femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 6 publications
2
53
2
Order By: Relevance
“…Although we did not observe these stems migrating, they were obviously exhibiting some lack of stability, which may be rotational [40]. Previous reported studies have suggested a positive predictive value of 50% for failure in patients with radiographic loosening [25]. We found the Accolade 1 stem demonstrated poor initial fixation in more than 1 . 3 of our patients, with continued progression of migration being a concern for its overall long-term clinical performance, especially for larger stems.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Although we did not observe these stems migrating, they were obviously exhibiting some lack of stability, which may be rotational [40]. Previous reported studies have suggested a positive predictive value of 50% for failure in patients with radiographic loosening [25]. We found the Accolade 1 stem demonstrated poor initial fixation in more than 1 . 3 of our patients, with continued progression of migration being a concern for its overall long-term clinical performance, especially for larger stems.…”
Section: Discussioncontrasting
confidence: 60%
“…Initial implant fixation is one of the key elements for a successful THA [21,35]. Consequently, migration analysis presents an early objective assessment of the predicted medium-to long-term performance and minimizes the risk of unexpectedly higher rates of later failure with early identification of at-risk components [10,13,25,28,29]. Having observed some early revisions for aseptic loosening of the Accolade 1 stem at our center, we set out to investigate the potential causes by evaluating initial implant stability using migration analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsidence of 2 mm or more in 2 years has been found to be predictive of implant failure within 5 years in hip surface arthroplasties (Beaule et al 2005). Several studies using the EBRA have demonstrated clearly that early migration predicts implant failure with high accuracy (Walker et al 1995, Kobayashi et al 1997, Biedermann et al 1999. In order to evaluate the fixation of cementless porous-coated stems in patients with osteonecrosis, we investigated 41 patients (41 hips) and compared our results with those of previously published studies dealing with cementless stems over a comparable follow-up time (Fye et al 1998, Hartley et al 2000, Kim et al 2003, Radl et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation may be that etiological factors of the osteonecrosis, such as steroid use and alcohol abuse, are associated with poor bone stock and potentially poor device fixation (Sarmiento et al 1990, Brinker et al 1994, Radl et al 2005. Measurement of stem subsidence is an accepted tool for evaluation of the quality of implant fixation whereas early migration indicates subsequent implant failure (Kobayashi et al 1997, Biedermann et al 1999). …”
mentioning
confidence: 99%